DAYA TARIK HERITAGE DAN FASILITAS WISATA SEBAGAI PEMICU MINAT KUNJUNGAN ULANG DI KOTA LAMA SEMARANG - Waruwu, Marniswati; Aryaningtyas, Aurilia Triani (Jurnal Pariwisata PaRAMA : Panorama, Recreation, Accomodation, Merchandise, Accessbility, 2024)
This study aims to analyze the influence of heritage attraction and tourism facilities on the intention to revisit the Old City of Semarang. The method used is a quantitative survey, with data collected through questionnaires distributed to 100 respondents. The results of the multiple regression analysis indicate that both heritage attraction and tourism facilities have a positive and significant impact on the intention to revisit. The heritage attraction, which includes aspects of architecture, history, and local culture, successfully captures the interest of visitors, while adequate tourism facilities contribute to a pleasant travel experience. This research provides recommendations for managers and local governments to enhance the quality of facilities and maintain heritage preservation, thus increasing the intention to revisit. The novelty of this research lies in the joint analysis of both variables in the context of heritage tourism in Indonesia.